1997
DOI: 10.1159/000111235
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Brain Creatine Kinase Gene Is Low in Neuroblastoma Cell Lines

Abstract: The cytoplasmic creatine kinase (CKB) enzyme has a central role in the regeneration of ATP in the brain. We have shown previously that CKB mRNA levels in cultured primary rat brain astrocytes and oligodendrocytes are much higher than in primary neurons. It has been suggested that high CKB expression is essential for the energy-demanding functions of glial cells. Conversely, CKB may be repressed in most neuronal cells; however, CKB protein has previously been detected by immunohistochemistry in several distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

1997
1997
1999
1999

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(40 reference statements)
0
0
1
Order By: Relevance
“…In addition to high CKB expression in glial cells, a number of human tumors display elevated CKB [Gazdar et al, 1981;Kaye et al, 1987], However, our results would suggest that CKB is not elevated in all transformed cells, since CKB mRNA was undetectable in neuronal RT4-B8 cells, low in neuronal RT4-E5 cells and barely detectable in mouse Cl 300 neuroblastomas NS20Y and N1E-115 [Wilson et al, 1997], Since we have recently shown in transient transfection experiments that tran scription of rat CKB is significantly repressed by the p53wt, tumor suppressor protein but not mutant p53 [Zhao et al, 1994[Zhao et al, , 1996, increased CKB may be a charac teristic of tumor cells which have lost p53wt function. Future investigations with RT4 cells, in conjunction with studies of primary cultures of neuronal and glial cells, will assist in identify the protein factors [Hobson et al, , 1990 regulating CKB expression in the PNS and CNS.…”
Section: Discussioncontrasting
confidence: 53%
“…In addition to high CKB expression in glial cells, a number of human tumors display elevated CKB [Gazdar et al, 1981;Kaye et al, 1987], However, our results would suggest that CKB is not elevated in all transformed cells, since CKB mRNA was undetectable in neuronal RT4-B8 cells, low in neuronal RT4-E5 cells and barely detectable in mouse Cl 300 neuroblastomas NS20Y and N1E-115 [Wilson et al, 1997], Since we have recently shown in transient transfection experiments that tran scription of rat CKB is significantly repressed by the p53wt, tumor suppressor protein but not mutant p53 [Zhao et al, 1994[Zhao et al, , 1996, increased CKB may be a charac teristic of tumor cells which have lost p53wt function. Future investigations with RT4 cells, in conjunction with studies of primary cultures of neuronal and glial cells, will assist in identify the protein factors [Hobson et al, , 1990 regulating CKB expression in the PNS and CNS.…”
Section: Discussioncontrasting
confidence: 53%